The Changes in the Use of IT on Building Product Information in the Turkish Construction Industry - Tas, Elcin; Cakmak, Pinar Irlayici (Elsevier BV, 2015)
AbstractIn Turkey, the use of IT on building product information has been discussed since 2002 at Istanbul Technical University, in the research projects BMIS and BMIS-II. In the progress of the research projects, two large scale field surveys were conducted both with the supply side - building product manufacturers and the demand side - design professionals in the years 2002 and 2010. The purpose of this paper is to describe the use and the importance of information technology by determining the changes in the behaviors and perspectives of the supply side and the demand side on building product information. In this context, the most significant results from the field surveys are presented by making comparisons between the situation in 2002 and 2010.
Keywords: Building Product Information; Demand Side; Turkish Construction Industry; Supply Side; Information Technology